Innovative Ideas and Gender (In)Equality - Koffi, Marlène (American Economic Review, 2025)
This paper analyzes recognition of women's innovative ideas compared to men's using bibliometric data in economics, mathematics, and sociology. I establish similarities between papers to construct relevant counterfactual citations. On average, all-female papers receive 10 percent fewer citations than all-male papers, a disparity reduced by 40 percent when considering team sizes and disappearing in most fields with authors' publication records. Additionally, strong in-group preferences emerge: All-male teams omit more papers with women, and vice versa. Accounting for publication histories, female scholars are cited 0 percent (economics) to 11 percent (mathematics) less, with early-career women enduring a 9–14 percent citation penalty. (JEL A14, C45, I23, J16)